Catalyst Particle Porosity Effect upon Flameless Combustion Characteristics - Kalinchak, V. V.; Chernenko, A. S.; Fedorenko, A. V.; Sofronkov, A. N.; Kramarenko, V. V. (Physics and Chemistry of Solid State, 2020)
The problem of heat and mass transfer of a porous catalyst particle is considered. On the her surface, including the inner surface of the pores, an irreversibly heterogeneous first-order reaction proceeds. It has been analytically shown that in a heated gas mixture, the catalyst's porosity reduces the minimum impurity's concentration of catalytic spontaneous combustion in the mixture and increases the catalyst particle's corresponding diameter. This concentration corresponds to the external kinetic and internal diffusion reaction's modes.